Monetary policy effects on bank loans in Germany: A panel-econometric analysis - Andreas Worms (Deutsche Bundesbank, 2001)
A crucial condition for the existence of a credit channel through bank loans is that monetary policy should be able to change bank loan supply. This paper contributes to the discussion on this issue by presenting empirical evidence from dynamic panel estimations based on a dataset that comprises individual balance-sheet information on all German banks. It shows that the average bank reduces its lending more sharply in reaction to a restrictive monetary policy measure, the lower its ratio of short-term interbank deposits to total assets is. This result is robust against a broad variety of changes in the specification. A dependence on its size can be found only if explicitly controlled for this dominating effect and/or if the very small banks are excluded. Overall, the evidence is compatible with the existence of a credit channel, although it is weakened by the banks' liquidity management. – – Eine wesentliche Bedingung für die Existenz eines durch Bankkredite wirkenden Kreditkanals ist, dass geldpolitische Maßnahmen das Bankkreditangebot verändern. Dieses Papier trägt zur Diskussion über diese Fragestellung bei, in dem es empirische Evidenz aus dynamischen Panelschätzungen präsentiert, die auf Bilanzdaten aller deutschen Banken basieren. Das Papier zeigt, dass die durchschnittliche Bank ihre Kreditvergabe in Reaktion auf eine restriktive geldpolitische Maßnahme um so stärker reduziert, je geringer der Anteil der von ihr gehaltenen kurzfristigen Interbankdepositen an ihrer Aktivsumme ist. Dieses Resultat ist robust hinsichtlich einer Vielzahl von Änderungen in der Schätzspezifikation. Eine Abhängigkeit der Reaktion von der Größe einer Bank kann nur dann festgestellt werden, wenn dieser dominierende Einfluß der kurzfristigen Interbankdepositen explizit berücksichtigt wird und/oder wenn die kleinen Banken von der Untersuchung ausgeschlossen werden. Alles in allem ist diese Evidenz kompatibel mit der Existenz eine Kreditkanals, obwohl dieser durch das Liquiditätsmanagement der Banken geschwächt wird.
Keywords: G21; C23; E52; 330; monetary policy transmission; credit channel; dynamic panel data; Transmissionsmechanismus; Kredit; Bankbilanz; Panel; Schätzung; Deutschland; credit channel